The Role Of Visum Et Repertum As Evidence In Rape Cases - Sukrisno, Adi; Triadi, Irwan (DiH: Jurnal Ilmu Hukum, 2025)
Visum and repertum is one of tool very important evidence in the process of enforcement law criminal, especially in case rape in general own difficulty proof consequence lack of witness eyes and often occurs in the space private. In context this, visa functioning as proof scientific that can confirm existence act violence sexual through findings medical objective, such as wound physical, damage to the reproductive organs, or footsteps biological perpetrators. Research This aiming for analyze in a way deep role strategic visa and report in proof law to case rape in Indonesia, as well as identify obstacles that affect its effectiveness. Method research used​ is approach legal normative and juridical empirical. Approach legal normative done with analyze provision law positive laws in force, such as the Criminal Code (KUHP) and the Law Number 8 of 1981 concerning Criminal Procedure Law (KUHAP), while approach legal empirical done through studies field, including interview with apparatus enforcer law like police and prosecutors, as well as power medical forensics involved​ direct in the process of making visa. Research results show that visa and report own position strategic in proof elements act criminal rape, especially in prove element violence or threat violence as well as the occurrence connection sexual without victim's consent. Although thus, the effectiveness visa often hampered by various​ factors, including delays​ reporting by victims due to trauma or shame, lack of victim's understanding of urgency inspection medical quick after events, and limitations power experts and means infrastructure forensics in the regions isolated.